2018
DOI: 10.1002/pssa.201800287
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Alumina Hyperbolic Metafilms with High‐Temperature Stability, Wide Wavelength Tunability, and Omnidirectional Absorption

Abstract: The authors report high-temperature stable, spectrally tunable, Pt/alumina hyperbolic metafilms with broadband absorption. Two uniform pairs of Pt (10 nm)/alumina (100, 150, or 200 nm) multilayer films with a top alumina passivation layer and a bottom Pt mirror and are prepared on sapphire substrates by sputtering. These Pt/alumina multilayer films yielded strong light absorption at visible to near-infrared wavelengths that are spectrally tunable by modulating the thickness of each alumina layer. Based on effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Engineering absorptivity/emissivity spectra at multiscale wavelengths enable thermal emission-harnessed energy devices including solar steamers, , radiative coolers, high-efficiency incandescent lamps, and thermophotovoltaics (TPVs). Each device is tailored to a different spectral range that relies on its working temperature and function. For example, radiative coolers working at room temperature, which present the possibility for the development of passive, heat dissipation technologies, are emissive at mid-infrared wavelengths (i.e., 5–30 μm, corresponding to the blackbody spectrum at room temperature).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering absorptivity/emissivity spectra at multiscale wavelengths enable thermal emission-harnessed energy devices including solar steamers, , radiative coolers, high-efficiency incandescent lamps, and thermophotovoltaics (TPVs). Each device is tailored to a different spectral range that relies on its working temperature and function. For example, radiative coolers working at room temperature, which present the possibility for the development of passive, heat dissipation technologies, are emissive at mid-infrared wavelengths (i.e., 5–30 μm, corresponding to the blackbody spectrum at room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if radiative coolers are designed to cool outdoor objects such as buildings, automobiles, and antennas, they must be reflective in the solar spectrum (0.3–2.5 μm). In comparison, solar steamers working at approximately 100 °C maintain unity absorptivity in the solar spectrum but must suppress their emissivity within the blackbody spectrum at such temperatures to minimize the radiative cooling effect. , TPVs are a class of electricity-generating systems without moving parts, thus enabling off-grid, portable, and ultralight power generators for drones, recreational vehicles, and spacecraft. Because most TPVs operate at high temperatures (>800 °C), spectral management of the emissions is necessary within the visible and near-infrared regions (typically 0.5–1.7 μm); the upper and lower cutoff wavelengths are determined by the band gap of the photovoltaic cells and the temperature of the emitters, respectively. An ideal TPV emitter exhibits a stepwise blackbody spectrum that is matched with the effective wavelength range. Therefore, the development of spectrally engineered, thermally stable emitters furthers the economic viability of TPVs.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) metal/dielectric subwavelength-pitch periodic patterns, frequently referred to as hyperbolic metamaterials, have a wide range of unconventional optical characteristics, including frequency-selective light absorption [1,2], perfect light transmission at a specific frequency and polarization [3], enormous Purcell factor enhancement [4], optical cloaking [5], and super-resolution imaging [6]. In addition, 1D hyperbolic metamaterials lead to the development of ultrathin, uniaxial birefringent films because they exhibit markedly different material dispersions depending on the in-plane polarization state (transverse electric, TE, or transverse magnetic, TM) of incident light [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stability of the selective emitters is one of the key issues in thermophotovoltaics (TPV) [1][2][3][4][5][6][7][8] . TPV provides a viable solution for efficient heat to power conversion, offering theoretical conversion efficiencies up to 85% 2,[9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…However, these working conditions are economically not viable in the commercialization of TPV technology. At medium vacuum condition of 10 −2 mbar, which can be achieved without turbomolecular pump, the thermal stability of metal-based emitters drastically decreases at high temperatures 1,7,26,36 . For example, we have shown that 1D multilayered metamaterial emitters from W-HfO 2 nanolayers can be thermally stable only up to 1000 °C under 10 −2 mbar medium vacuum pressure 1,36 .…”
mentioning
confidence: 99%